Effect of spacing on some mechanical properties of narrow leaved ash (Fraxinus angustifolia) wood - Guler, Cengiz; Ibrahim Sahin, Halil; Aliogullari, Serdar (Maderas. Ciencia y Tecnología, 2025)
In this study, conducted to test the effect of spacing on wood quality; the effect of four different spacing types, applied in Adapazarı Süleymaniye plantation (Region 1; 3x2 m; Region 2; 3x2,5 m; Region 3; 3,75x3,75 m; Region 4; 4x4 m), on some mechanical properties of narrow leaved ash (Fraxinus angustifolia) have been studied. In the present study, some mechanical properties such as the compression strength parallel to grain, tensile stress perpendicular to grain, bending strength, impact bending strength and modulus of elasticity were determined. As a result, the ash wood, grown in region 4 with a wide range of planting, has high mechanical properties. However, when analyzed in terms of wood quality characteristics, it has been found that spacing in region 1 (2x3 m) is more suitable for applications of ash plantations.